Implementasi Model Pembelajaran Problem Based Learning Dalam Pembelajaran Pendidikan Jasmani Di SMA Negeri 4 Karawang - Rahmayanti Dewi; Resti Gustiawati; Rolly Afrinaldi (Journal Coaching Education Sports, 2020)
The aim of this study is to find out how the implementation of the model of learning problem based learning at SMA Negeri 4 Karawang. This reseacrh uses a qualitative approach and a qualitative descriptive study method. This observation was done at SMA Negeri 4 Karawang and the population was taken from second geade of them where each class was represented by one student. The number of informants were five students and one teacher. The sample technique used is Snowball Sampling. This research demonstrates that the learning process that has been used is running well. The Problem Based Learning model is lack effective in Physical Education learning process at SMA Negeri 4 Karawang because the teacher said that students do not all have the same abilities, especially for the lazy and less active students will leave the student saturated and less enthusiastic during the learning process